Effect of residual toxicity of selected insecticides to the Malaysian stingless bee Heterotrigona Itama / Noor Albannia Natasya Jabi and Hazmi Awang Damit - Jabi, Noor Albannia Natasya; Awang Damit, Hazmi (Universiti Teknologi MARA, Sabah, 2019)
Heterotrigona itama is a Malaysian stingless bee species that actively reared for meliponiculture. This stingless bee is cultivated in a commercial scale for its honey production, propolis and among the greatest commercial potential as crop pollinators. However, this species has been potentially exposed to agronomic practices, among which the use of synthetic insecticides against pests. The indirect toxicity effect of the post-insecticide had affected the mortalities of H. itama especially, to the foragers. Due to that, a study has been conducted to determine the lethal concentration of 50% (LC50) and 95% (LC95) of the selected insecticides against stingless bee forager workers through residual exposure. The bioassay test was conducted to the local stingless bee H. itama at Agricultural Research Station, Tenom. Four commonly used insecticides in crop protection; Deltamethrin, Chlorpyrifos, Cypermethrin and Malathion were tested at five concentrations that diluted with 500 ml of distilled water in three replications for each insecticide. Lethal concentrations (LC50 and LC95) were obtained from probit analysis after 1-hour dry residues exposure and 24-hour mortality observation. The result shows that; all four tested insecticides were harmful to H. itama through dry residue. Deltamethrin shows the higher value of LC50 (1.256 ml) and LC95 (3.582ml) that make it less toxic to the H. itama than cypermethrin, malathion, and chlorpyrifos, however, as the concentration gets higher it becomes more toxic.